Metoda za povečanje robustnosti konstrukcijskega procesa v individualni proizvodnji - Varl, Mitja (visokošolska dela, 2020)
Increasing competition has forced companies to expand their product range to meet changing customer needs and requirements. The efficiency and robustness of the design process of an individual product must be ensured by an appropriate system of information and methodological support and the reorganization of process activities. The product development strategy must be based on the identification of customer requirements, embedded in the concept of modularity of physical functions, which enables individual product realization. This inevitably requires a transition to development of adaptable, modular products. Product modularity is achieved by combining different modules robustly connected through a common platform. This is the basis for setting up a smart factory, within which dynamic business and engineering processes enable last-minute design and manufacturing changes, allowing for an agile response in the event of any changes. This thesis presents a framework for transforming the development and design process within highly individualized business environment in accordance with agile and lean principles. Process robustness has been increased through the introduction of enhanced process and product variability and through the implementation of concurrent and smart design strategies. The presented framework has been validated by an extensive case study in a real industrial environment. The significant effects have confirmed the practical applicability of the proposed framework, while its generalized form allows its direct implementation into similar industrial environments, within which individualized products maximize their profitability due to their higher quality and shorter lead times.
Keywords: agilnost; digitalni dvojček; individualna proizvodnja; modularnost; razvojno-konstrukcijski procesi; robustnost; vitkost